2017
DOI: 10.4314/ahs.v16i4.30
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of Antiretroviral and African traditional medicines amongst people living with HIV/AIDS (PLWA) in the eThekwini Metropolitan area of KwaZulu Natal

Abstract: Background: People living with HIV/AIDS (PLWA) often use African Traditional Medicines (ATM) either alone or in combination with Western medicines including Antiretrovirals (ARV). Objective: To explore the prevalence of concurrent Antiretrovirals (ARV) and African Traditional medicines (ATM) use and determine the effects of any concurrent use on the CD4+ Lymphocyte count and Viral Load (VL) of PLWA in the eThekwini Metropolitan area. Methods: A descriptive and exploratory study was carried out on 360 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Subtherapeutic drug levels could lead to unsatisfactory viral suppression. Herbal products may also contain compounds that interfere with the absorption of antiretrovirals [ 86 ] Concurrent use of antiretroviral and African traditional medicines amongst people living with HIV/AIDS (PLWA) in the eThekwini metropolitan area of KwaZulu Natal KwaZulu-Natal Concurrent ARV and ATM use is quite low when compared to ATM use before HIV diagnosis and after HIV diagnosis but before initiation with ARV [ 87 ] Traditional, complementary and alternative medicine use by HIV patients a decade after public sector antiretroviral therapy roll out in South Africa: a cross sectional study KwaZulu-Natal The use of traditional, complementary and alternative medicine is prevalent amongst a small proportion of HIV infected patients attending public healthcare sector antiretroviral clinics [ 67 ] Antiretroviral therapy initiation and adherence in rural South Africa: community health workers' perspectives on barriers and facilitators KwaZulu-Natal There are a number of factors associated with non-adherence, which includes a dilemma between ART and alternative medicine use [ 75 ] Inhibition of CYP2B6 by medicinal plant extracts: implication for use of efavirenz and nevirapine-based highly active anti-retroviral therapy (HAART) in resource-limited settings Not indicated There is a high probability that standard doses affect drug plasma concentrations, which could lead to toxicity, when drugs that are metabolized by CYP2B6, are co-administered with herbal medicines [ 88 ] Concurrent use of traditional medicine and ART: perspectives of patients, providers and traditional healers in Durban, South Africa KwaZulu-Natal Some patients do not view TAM as an alternative to ART; rather, employ TAM and ART for distinctly different needs [ 89 ] The potential of Sutherlandia frutescens for herb–drug interaction Not indicated Herb–drug interactions have an effect on enzymes responsible for ART drug metabolism and transport [ 90 ] Why HIV positive patients on antiretroviral treatment and/or cotrimoxazole prophylaxis use traditional medicine: perceptio...…”
Section: Resultsmentioning
confidence: 99%
“…Subtherapeutic drug levels could lead to unsatisfactory viral suppression. Herbal products may also contain compounds that interfere with the absorption of antiretrovirals [ 86 ] Concurrent use of antiretroviral and African traditional medicines amongst people living with HIV/AIDS (PLWA) in the eThekwini metropolitan area of KwaZulu Natal KwaZulu-Natal Concurrent ARV and ATM use is quite low when compared to ATM use before HIV diagnosis and after HIV diagnosis but before initiation with ARV [ 87 ] Traditional, complementary and alternative medicine use by HIV patients a decade after public sector antiretroviral therapy roll out in South Africa: a cross sectional study KwaZulu-Natal The use of traditional, complementary and alternative medicine is prevalent amongst a small proportion of HIV infected patients attending public healthcare sector antiretroviral clinics [ 67 ] Antiretroviral therapy initiation and adherence in rural South Africa: community health workers' perspectives on barriers and facilitators KwaZulu-Natal There are a number of factors associated with non-adherence, which includes a dilemma between ART and alternative medicine use [ 75 ] Inhibition of CYP2B6 by medicinal plant extracts: implication for use of efavirenz and nevirapine-based highly active anti-retroviral therapy (HAART) in resource-limited settings Not indicated There is a high probability that standard doses affect drug plasma concentrations, which could lead to toxicity, when drugs that are metabolized by CYP2B6, are co-administered with herbal medicines [ 88 ] Concurrent use of traditional medicine and ART: perspectives of patients, providers and traditional healers in Durban, South Africa KwaZulu-Natal Some patients do not view TAM as an alternative to ART; rather, employ TAM and ART for distinctly different needs [ 89 ] The potential of Sutherlandia frutescens for herb–drug interaction Not indicated Herb–drug interactions have an effect on enzymes responsible for ART drug metabolism and transport [ 90 ] Why HIV positive patients on antiretroviral treatment and/or cotrimoxazole prophylaxis use traditional medicine: perceptio...…”
Section: Resultsmentioning
confidence: 99%
“…In addition, patients were more likely to continue ART when they were taking non-ACT anti-malaria medication or herbal remedies (which may explain why less educated patients were more likely to report continuing ART than their more educated counterparts).The association between continuing ART and using traditional or non-ACT medications may be due to patients experiencing fewer drug interactions when taking these alternative medications or to them perceiving alternative regimens as relatively safer or milder and, therefore, being less afraid of remaining on ART while taking them. Other studies in sub-Saharan Africa have found that HIV-infected patients do concurrently use herbal treatment while on ART for perceived minor ailments (including malaria) in the belief that it increases their energy and immunity [36]. Although the number of people using traditional medication to treat malaria is low in our sample (which is in keeping with the figures reported in other studies of patients on ART [36]), our findings suggest that there may be potential, under-appreciated risk of interaction between traditional medication and ART in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in sub-Saharan Africa have found that HIV-infected patients do concurrently use herbal treatment while on ART for perceived minor ailments (including malaria) in the belief that it increases their energy and immunity [36]. Although the number of people using traditional medication to treat malaria is low in our sample (which is in keeping with the figures reported in other studies of patients on ART [36]), our findings suggest that there may be potential, under-appreciated risk of interaction between traditional medication and ART in this population. The use of traditional medicines in patients who are taking ART and/or anti-malarial warrants further study, preferably using in-depth, qualitative methods that can better illuminate their beliefs and their decision-making processes than quantitative surveys such as ours.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported varying levels of concurrent TM and ARV use among PLWHIV and conflicting evidence of TM as a potential barrier to ART adherence (Naidoo, 2014; Hughes, Puoane, Clark, Wondwossen, Johnson, & Folk, 2012; Groh et al, 2011). One study in KwaZulu- Natal found that only 4.98% of 281 PLWHIV used TM and ARV concurrently (Sibanda, Nlooto, & Panjasaram, 2016). South African studies suggest a decrease in TM use among PLWHIV who commence ART (Moshabela et al, 2011; Peltzer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%